Disruption of tephra fall deposits caused by lava flows during basaltic eruptions. - Brown, R.J.; Thordarson, T.; Self, S.; Blake, S. (Bulletin of Volcanology, 2015)
Observations in the USA, Iceland and Tenerife, Canary Islands reveal how processes occurring during basaltic eruptions can result in complex physical and stratigraphic relationships between lava and proximal tephra fall deposits around vents. Observations illustrate how basaltic lavas can disrupt, dissect (spatially and temporally) and alter sheet-form fall deposits. Complexity arises through synchronous and alternating effusive and explosive activity that results in intercalated lavas and tephra deposits. Tephra deposits can become disrupted into mounds and ridges by lateral and vertical displacement caused by movement (including inflation) of underlying pāhoehoe lavas and clastogenic lavas. Mounds of tephra can be rafted away over distances of 100 s to 1,000 s m from proximal pyroclastic constructs on top of lava flows. Draping of irregular topography by fall deposits and subsequent partial burial of topographic depressions by later lavas can result in apparent complexity of tephra layers. These processes, deduced from field relationships, have resulted in considerable stratigraphic complexity in the studied proximal regions where fallout was synchronous or alternated with inflation of subjacent lava sheets. These mechanisms may lead to diachronous contact relationships between fall deposits and lava flows. Such complexities may remain cryptic due to textural and geochemical quasi-homogeneity within sequences of interbedded basaltic fall deposits and lavas. The net effect of these processes may be to reduce the usefulness of data collected from proximal fall deposits for reconstructing basaltic eruption dynamics.